2015
DOI: 10.5937/industrija43-9219
|View full text |Cite
|
Sign up to set email alerts
|

Impact of asset quality on bank profitability: Case study

Abstract: The paper explores the impact of asset quality on banks' profitability in the case of a commercial bank in Serbia. Parameters covered as key indicators of the impact on profitability are: maturity of the portfolio, clients ' ratings, NPL (Non-Performing)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This equation and close versions are used also by Ozurumba (2016), Ugoani (2016), Adebisi and Matthew (2015), Bhattarai (2016), Etale et al (2016), Lata (2014), Afiriyie and Akotey (2013) and Bace (2016). Likewise, by searching non-performing loans as the determinants of bank profitability under their studies, more extensive forms of the below stated equation is used (Buchory, 2015;Duraj & Moci, 2015;Güneş, 2015;Kasavica & Jović, 2015;Khan, Anuar, Choo, & Khan, 2011;Ozgur & Gorus;Samırkaş et al;Sarıtaş et al;Taşkın, 2011) , = + 1 2 , + 2 2 , + 3 2 , + ,…”
Section: Methodsmentioning
confidence: 99%
“…This equation and close versions are used also by Ozurumba (2016), Ugoani (2016), Adebisi and Matthew (2015), Bhattarai (2016), Etale et al (2016), Lata (2014), Afiriyie and Akotey (2013) and Bace (2016). Likewise, by searching non-performing loans as the determinants of bank profitability under their studies, more extensive forms of the below stated equation is used (Buchory, 2015;Duraj & Moci, 2015;Güneş, 2015;Kasavica & Jović, 2015;Khan, Anuar, Choo, & Khan, 2011;Ozgur & Gorus;Samırkaş et al;Sarıtaş et al;Taşkın, 2011) , = + 1 2 , + 2 2 , + 3 2 , + ,…”
Section: Methodsmentioning
confidence: 99%
“…There are plenty of researches measuring the impact of asset quality on bank profitability (for example -Kasavica, Jović, 2015). However, in the relevant literatures it is not developed a model designed to determine the effects of of implementation SEPA rules on the performance of the banking sector.…”
Section: Sepa-compatible Instruments -Efficiency Measures Of the Implmentioning
confidence: 99%
“…The study found that net interest margin does reflect a premium to compensate for the risk of loan default (Kasavica & Jovic, 2015). In addition, the study showed that large banks had higher sensitivity to the risk of default than smaller banks (Kasavica & Jovic, 2015).…”
mentioning
confidence: 93%
“…Typically, riskier loans carry higher interest rates along with a higher provision for default than high quality loans. A study by Kasavica and Jovic (2015) examined whether banks with a risky loan portfolio specifically selected higher interest rates on those loans to achieve a higher net interest margin and compensate for the loan portfolio risk. The study found that net interest margin does reflect a premium to compensate for the risk of loan default (Kasavica & Jovic, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation